2006
DOI: 10.1016/j.pneurobio.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral benzodiazepine receptor (Translocator protein 18kDa) in microglia: From pathology to imaging

Abstract: Microglia constitute the primary resident immune surveillance cell in the brain and are thought to play a significant role in the pathogenesis of several neurodegenerative disorders such as Alzheimer's disease, multiple sclerosis, Parkinson's disease and HIV-associated dementia. Measuring microglial activation in vivo in patients suffering from these diseases may help chart progression of neuroinflammation as well as assess efficacy of therapies designed to modulate neuroinflammation. Recent studies suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
330
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 340 publications
(339 citation statements)
references
References 139 publications
3
330
0
5
Order By: Relevance
“…Inflammation can be associated with several fold increased densities of PBRs (Venneti et al, 2006). We performed Monte Carlo simulations to investigate if such large increases in receptor binding could be measured accurately in vivo with [ 11 C]PBR28.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation can be associated with several fold increased densities of PBRs (Venneti et al, 2006). We performed Monte Carlo simulations to investigate if such large increases in receptor binding could be measured accurately in vivo with [ 11 C]PBR28.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…An area with high density of glia or significant inflammation may have several fold increased density of PBRs (Venneti et al, 2006). Therefore, in addition to measuring low density of receptors found in healthy human brain, a useful PET radioligand must also be able to measure areas of increased binding.…”
Section: Simulations Of Increased Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…TSPO is present on the outer mitochondrial membrane of microglia, and one established function of TSPO is to transport cholesterol to the inner mitochondrial membrane for the production of steroids, with possible additional functions in regulating cell death, cytokine production, and microglial proliferation (20). Recent studies have also found that TSPO itself has a role in regulating microglial immune function, as antagonists of TSPO reduce the activation of microglia (21).…”
mentioning
confidence: 99%
“…Nearly 30 years ago, radiolabeling of the prototypic PBR/TSPO ligand PK11195 with carbon-11 enabled in vivo imaging of microglial activation using Positron Emission Tomography (PET scan) (Camsonne et al, 1984), and paved the road for neuroinflammation imaging. However, [ 11 C]PK11195 has shown limitations that until now slowed clinical application of neuroinflammation imaging by PET (Venneti et al, 2006). Although the field is still very active, as seen from the plethora of radioligands for PBR/TSPO that have been radiolabeled these last few years (Chauveau et al, 2008), large-scale clinical PET studies are difficult to set up in the context of emergency stroke management.…”
Section: Introductionmentioning
confidence: 99%